Expert political risk opinions and banking system returns: A revised banking market model. - Simpson, John (2007)
Human behaviour in banking and finance systems is in part made up of a complex mix of political, social and cultural factors. These factors are reflected in expert opinion based political risk scores. Market inefficiency is largely a result of anomalies in human behaviour causing information asymmetries. A basic systemic market model is re-specified into a model for international banking systems, which controls for pure political risk. Samples of developed and developing banking systems are examined. Political risk factors and world banking returns are exogenous in models of country-banking system returns. New political information assists in explaining banking system stock returns. The findins should be of interest to investors in banking stocks. Banking regulators may be assisted in decisions on appropriate levels of regulatory capital as a benchmark for banking systems. The model could help to anticipate financial crises.